Olfaction and Taste: Invasive Odours and Disappearing Objects - Borthwick, Fiona (The Australian journal of anthropology, 2000)
The metaphorisation of sight and hearing, the objective senses, dominate the founding ideas, or philosophemes, of Western philosophy. The senses of taste and smell are of little relevance in the formation of conceptual knowledge or in classificatory systems; they are, by virtue of their dissolving objects, incapable of giving objective knowledge in Western metaphysics. Derrida and Ulmer developed a metaphorology that exploits the chemical basis of the subjective senses of taste and smell. The anthropology of the senses takes this questioning of metaphysics into issues of how olfaction and taste function in sociality. In the routine practices of everyday life, is olfaction able to create the sense of community that it does in rituals? Or, has the repression of smell in humanity's evolution towards ‘civilisation’ muted the connective ability of multiple odour particles? In a culture and metaphysics that presumes the separability of the self from the other and the self from the object, is there a place for senses that make a nonsense of separation and objectivity through their state of meaningful dissolution? Through philosophy's metaphorisation, has taste been stripped of its sensuousness and made a sense for aesthetics and not flavours and textures? In a metaphorics premised in judgement and discernment, can taste be a sense that founds sociality? In blurring the boundaries between self and other that are necessary to form and maintain the distinction, the dissolvability of smell and taste makes another metaphorics and other socialities possible. Of all the senses, that of smell—which is attracted without objectifying—bears clearest witness to the urge to lose oneself in and become the ‘other’. As perception and the perceived—both are united—smell is more expressive than the other senses (Horkheimer and Adorno 1979:184).